PEMBELAJARAN QUANTUM TEACHING DENGAN PENDEKATAN MULTI KECERDASAN UNTUK MENINGKATKAN HASIL BELAJAR FISIKA - Zuhdi Ma’aruf; Siti Salamiah (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2008)
The purpose of this research was to described result learn student physics at rectilinear motionkinematics discussion fundamental with applying quantum teaching by multi intellegences. The subject of theresearch is the student X3 class of SMA N 1 Kampar the sample taken was 37 student. Research instrumentused of collecting data in this research is result of learning test, and data analysis by descriptive analysis isabortive power, learn effectiveness, completeness of student’s study, completeness of indicator, assessment ofaffective, and assessment of psikomotor. The result of data analysis shows average of student’s abortivepower is 79,05% with good category, learn effectiveness 79,05%, completeness of student’s learns purposewith complete category and completeness of indicator is 77,78%. For the assessment of affective categorizedis good enough ( 75,68%) and assessment of psychomotor categorized is goodness ( 40,54%).Keyword: Result Learn, Quantum Teaching, Multi Intellegence